2020
DOI: 10.3389/fphar.2020.00860
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Polymorphisms Involved in Platelet Activation and Inflammatory Response on Aspirin-Related Upper Gastrointestinal Bleeding: A Case-Control Study

Abstract: Background: Despite the wide benefits of aspirin and its cost-effectiveness, aspirin prescriptions have been reduced due to idiosyncratic responses in susceptible individuals. Low-dose aspirin and single-nucleotide polymorphisms (SNPs) are independently associated with increased risk of gastrointestinal hemorrhage; however, to-date, no studies investigated the SNP-aspirin interaction effect on upper gastrointestinal hemorrhage (UGIH). Therefore, we aimed to evaluate the role of 25 SNPs in multiple genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Regarding population variability, ethnicity and ancestry are important factors that directly influence in the genetic variability among different populations (29,30) . In this context, some studies identified genetic susceptibility to the incidence of NVUGIB secondary to peptic ulcer disease (14,17,18) , as well as for rebleeding episodes (31) . Besides, use of LDA and NSAIDs in patients who have genetic variants in the CYP2C9 (17,32) and VKOCR1 (24) , genes responsible for these drugs metabolism, might lead to an additive interaction and enhance the risks of NVUGIB secondary to peptic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding population variability, ethnicity and ancestry are important factors that directly influence in the genetic variability among different populations (29,30) . In this context, some studies identified genetic susceptibility to the incidence of NVUGIB secondary to peptic ulcer disease (14,17,18) , as well as for rebleeding episodes (31) . Besides, use of LDA and NSAIDs in patients who have genetic variants in the CYP2C9 (17,32) and VKOCR1 (24) , genes responsible for these drugs metabolism, might lead to an additive interaction and enhance the risks of NVUGIB secondary to peptic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Through a recent systematic review (2020) ( Forgerini et al, 2021a ), three studies that evaluated single-nucleotide polymorphisms (SNPs) in the PTGS1 and NOS3 genes and the UGIB risk were identified ( van Oijen et al, 2006 ; Wu et al, 2016 ; Mallah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Wu et al evaluated this same SNP and two others (rs1330344 and rs3842788), and association data were only reported for the rs1330344 variant, which identified an increased risk of UGIB in homozygous patients (OR: 2.17, CI 95%: 1.01–4.66) ( Wu et al, 2016 ). Finally, Mallah et al (2020) evaluated three SNPs in the PTGS1 gene (rs1330344, rs384287, and rs5788) and one SNP in the NOS3 gene (rs1799983). The risk of UGIB was identified in LDA users and in the presence of CT + TT (rs1330344) (OR: 4.02, CI 95%: 1.11–14.54) and GT + TT genotypes (rs1799983) (OR: 7.690, CI 95%: 2.4–23.7) ( Mallah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent preliminary study by Mallah et al identified polymorphisms in platelet activity, angiogenesis and inflammatory response genes were associated with aspirin-related UGIB ( Mallah and et al, 2020 ), building on the findings of previous investigations ( Shiotani et al, 2010 ; Shiotani and et al, 2013 ; Shiotani et al, 2014 ; Wu et al, 2016 ; Cho and et al, 2016 ; Milanowski et al, 2017 ). The group identified “positive markers,” that indicated an increased risk of aspirin related UGIB and protective “negative markers” which decreased the risk ( Mallah and et al, 2020 ). Of particular interest, rs689466 T > C, a SNP in the COX-2 gene was associated with an increased risk of UGIB ( Mallah and et al, 2020 ).…”
Section: Genetic Risk Factorsmentioning
confidence: 92%
“…The group identified “positive markers,” that indicated an increased risk of aspirin related UGIB and protective “negative markers” which decreased the risk ( Mallah and et al, 2020 ). Of particular interest, rs689466 T > C, a SNP in the COX-2 gene was associated with an increased risk of UGIB ( Mallah and et al, 2020 ). However, these data are preliminary and need to be replicated in other cohorts.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%